Impact of Emerging Technologies on Educational Business Models: A Quantitative Approach - Cobos Gutierrez, Carlos Eduardo (2024)
The adoption of technologies such as artificial intelligence, augmented reality, and digital learning platforms has been a key factor in driving this shift. The study found a positive correlation between the use of emerging technologies and improvements in global competitiveness and administrative efficiency. However, challenges like the digital divide and resistance to change need to be addressed to fully leverage the benefits of digital transformation.